Anagram Based L2 Activation - LENGYEL, ZSÃ“FIA (Indonesian Research Journal in Education |IRJE|, 2019)
The aim of the present study is to investigate the Hungarian-English word recognition among sixty of 15 years old, Hungarian, secondary school students, who learn English as the first foreign language. Moreover to ascertain how English and Hungarian languages become activated in a paper based word recognition test including anagrams. Based on the literature, I suppose that instructed English language learners recognize the first language (Hungarian) input more successfully. On the top of all that I am eager to see the various factors that affect word recognition. The results show that word frequency effect is a key factor irrespective of the language proficiency.